Hyperbaric Oxygen Suppresses Hypoxic-Ischemic Brain Damage in Newborn Rats. (January 2015) - Zhu, Min; Lu, Mengru; Li, Qing-jie; Zhang, Zhuo; Wu, Zheng-zheng; Li, Jie; Qian, Lai; Xu, Yun; Wang, Zhong-yuan
The optimal therapeutic time-window and protective mechanism of hyperbaric oxygen in hypoxic-ischemic brain damage remain unclear. This study aimed to determine the neuroprotective effects of hyperbaric oxygen. Following hypoxic-ischemic brain damage modeling in neonatal rats, hyperbaric oxygen was administered at 6, 24, 48, and 72 hours and 1 week after hypoxia, respectively, once daily for 1 week. Fourteen days after hypoxic-ischemic brain damage, cell density and apoptosis rate, number of Fas-L+, caspase-8+, and caspase-3+ neuronal cells, levels of nitric oxide, malondialdehyde, and superoxide dismutase in hippocampus were examined. Morris water maze test was conducted 28 days after insult. Significant improvements were found in cell density, rate of apoptosis, oxidative stress markers, FasL, and caspases in rats treated with hyperbaric oxygen within 72 hours compared to hypoxic-ischemic injury. Similarly, time-dependent behavioral amelioration was observed in pups treated with hyperbaric oxygen. Our findings suggest that hyperbaric oxygen protects against hypoxic-ischemic brain damage by inhibiting oxidative stress and FasL-induced apoptosis, and optimal therapeutic time window is within 72 hours after hypoxic-ischemic brain damage.